Scholarly Use of Electronic Resources: A Study of Citations and References Cited in Electronic Journal Articles. - Kim, Hak Joon (2009)
A study was conducted using 2,734 citations and references to electronic resources cited in 94 scholarly and peer reviewed ejournals published between 2005 and 2008. Study illustrated problems that occur when users attempt to access e-sources cited in e-journal articles.
Keywords: dept.ils; faculty_collection; sabbatical_report

Digital Libraries, Its Theory and Practices. - Liu, Yan Quan (2009)
Thirteen chapters and 47 sections of the book"Digital libraries, its theory and practices" were worked on and the book is ready to send to the publisher. Did a paper that was accepted by the journal Library Hi Tech. Visited China and gave 2 seminars in 2 universities in China.
Keywords: dept.ils; faculty_collection; sabbatical_report

Storytelling: Interdisciplinary Applications for the Elementary Curriculum. - Nowlan, Gwendolyn (2002)
Keywords: dept.ils; faculty_collection; sabbatical_report

Needs Assessment Survey Instrument to Identify Library Support Needs for on-Line Master of Library Science Students at Southern Connecticut Sate University. - Okobi, Elsie Rogers Halliday (2002)
Keywords: dept.ils; faculty_collection; sabbatical_report

A Dictionary of Quotations and Proverbs About Cats and Dogs - Nowlan, Robert A.; Nowlan, Gwendolyn Wright (McFarland, 2001)
Keywords: Cats; Quotations; maxims; etc; Quotations; maxims; etc; Dogs; dept.ils; dept.mat; faculty_collection

A Dictionary of Quotations About Communication - Nowlan, Robert A.; Nowlan, Gwendolyn Wright (McFarland, 2000)
Keywords: Quotations; Quotations; English; dept.ils; dept.mat; faculty_collection

International and Comparative Studies in Information and Library Science: A Focus on the United States and Asian Countries - Liu, Yan Quan; Cheng, Xiaojun (Scarecrow Press, 2008)
Keywords: Asia; Asia; Information science; Comparative librarianship; International librarianship; Library science; United States; Information science; United States; Library science; dept.ils; faculty_collection

Exhibits in Libraries: A Practical Guide - Brown, Mary E.; Power, Rebecca (McFarland & Co., 2006)
"Library exhibits can inspire and educate, stimulate an interest that can be explored in a book, or attract visitors who otherwise wouldn't stop by. Displays are an opportunity to put a creative foot forward or help patrons navigate the facility. This "how-to" includes everything a librarian needs to know to put on an exhibit"–Provided by publisher.
Keywords: Handbooks; manuals; etc; Library exhibits; dept.ils; faculty_collection

Libraries Designed for Users: A 21st Century Guide - Lushington, Nolan (Neal-Schuman Publishers, Neal-Schuman, 2002)
Keywords: Library buildings; Planning; Library architecture; Libraries; Space utilization; dept.ils; faculty_collection

We better get this party started! - Lavoie, L.; Markiewicz, J. (College and Undergraduate Libraries, 2006)
Each fall, the Tunxis Library hosts a party. Usually thematic, sometimes didactic, and always cerebral, the library uses the party to communicate our “party line” to the entire campus community: we are here to make your life easier. It's particularly effective when delivered at the start of the semester, before the unrelenting rhythm of classes, committee work, and meetings has begun. Showing the campus community that the library is here to support them is our core theme, wrapped in a party context. Our goal is to create a party that jump-starts the fall semester for everyone. In this article, we describe our most recent parties, focusing how we develop, plan, and execute these promotional initiatives, with little money, but plenty of creativity and teamwork. © 2005 by The Haworth Press, Inc. All rights reserved.
2 citations (Crossref) [2023-10-31]
Keywords: Community colleges; Library marketing; Library promotion; Parties; Teams; dept.ils

Evaluation of federated searching options for the school library - Abercrombie, S.E. (School Library Media Research, 2008)
Three hosted federated search tools, Follett One Search, Gale PowerSearch Plus, and WebFeat Express, were configured and implemented in a school library. Databases from five vendors and the OPAC were systematically searched. Federated search results were compared with each other and to the results of the same searches in the database's native interface to disclose differences in handling query syntax, searching, retrieval, browsing results, etc. Each product was easily configured, but none were capable of searching every database desired. Simpler Boolean queries are the most successful queries because of the underlying structure and differences of the databases, and the capabilities of certain products. Federated search products succeed in simplifying access to multiple database resources at school, but searching remains different from the familiar Web search engines in many ways. To become more Google-like, federated searching must be done against indexes built in advance instead of the current real-time searching method.
Keywords: dept.ils; ⛔ No DOI found

Citation searching: Search smarter & find more - Hammond, C.C.; Brown, S.W. (Computers in Libraries, 2008)
All in all, citation searching is a wonderful way to build a comprehensive body of knowledge. The databases allow you to follow a trail of cited references that weaves a web of information across the boundaries of time and subject limitations. It eliminates your need to know appropriate synonyms or subject-specific lingo in order to perform effective searches that yield inclusive results. Citation searching saves time while also increasing the likelihood that your search results will be appropriate for your needs. Citation searching is not just useful for librarians but for other searchers as well. If you need a comprehensive literature review - whether you're a librarian, faculty member, student, or scientist - you would benefit greatly from the capabilities of citation searching databases. The training program for citation searching at the University of Connecticut taught graduate students all these tricks and more. Students who attended our sessions now know how to do broad, interdisciplinary searches after they have searched their primary subject database. They also understand how to "chain" from the original article to the "backward" citations in that article and to the "forward" articles that cited the original. Finally, they see how they can use citation databases to find information about who's citing their articles, which they can use for job searching and grant proposals, promotion, and tenure. Try it yourself - you're sure to find something new!
Keywords: dept.ils; ⛔ No DOI found

Gender distinctiveness, communicative competence, and the problem of gender judgments in computer-mediated communication - Sierpe, Eino (Computers in Human Behavior, 2005)
Despite persistent claims regarding the ability of text-based computer-mediated communication to neutralize gender identities, few researchers have worked on the problem of gender distinctiveness in textual production and interpretation, gender judgments, and more importantly, the role of gender in the process of impression formation in electronic communication. Against this background, the author addresses the theoretical aspects of gender in textual communication and places the problem of gender distinctiveness and gender judgments in CIVIC in the context of Hymes' model of communicative competence. He also isolates several variables worthy of investigation, namely, the provision of gender judgments, accuracy, and certainty. He then reconceptualizes the problem of gender distinctiveness and impression formation in CIVIC by bridging the gap between textual markedness and expectations. (C) 2003 Elsevier Ltd. All rights reserved.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/055-557-328-035-914 tex.type: [object Object]
Keywords: Communicative competence; Computer-mediated communication; Electronic communications; Formal languages; Gender judgments; Linguistics; Problem solving; Research; dept.ils; peer-reviewed

Power information user model presents worthy premise but flawed methodology (multiple letters) - Iwema, C.L.; Sathe, N.; Lee, P.; Giuse, N. (Journal of the Medical Library Association, 2005)
Keywords: Community-Institutional Relations; Health Education; Humans; Inservice Training; Models; Organizational; Research Design; Tennessee; dept.ils; health care personnel; information dissemination; letter; library; library science; medical informatics; medical information system; methodology; public health; research; ⛔ No DOI found

Distance education and the new MLS: The employer's perspective - Kim, Hak Joon; Kusack, James Michael (Journal of Education for Library and Information Science, 2005)
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/020-066-399-143-203 tex.type: [object Object]
Keywords: dept.ils

The present and future of China's National Science and Technology Library - A new paradigm of sci-tech information resource sharing - Meng, Liansheng; Liu, Yan Quan (New Library World, 2005)
Purpose - The purpose of this case study is to explore the construction pattern and issues involved with the development of the National Science and Technology Library (NSTL) in China. Design/methodology/approach - This study was conducted through an analytical evaluation of the historical development of scientific and technological information sharing among libraries and information centers and issues around construction of the NSTL. Findings - Since the establishment of its network service system at the end of 2000, the NSTL has made rapid progress in constructing a sci-tech information resource sharing system and offering web-based information services to the patrons of scientific and technical communities all over China. Originality/value - This paper is the first exploration that brings to the forefront the foundational background of the NSTL, the characteristics of its organizational structure, the functions of its service, and the tentative plan to increase its accessibility and usability. Symptomatic of the function of the NSTL constructing pattern will hopefully shed light not only to the reformation of the Chinese sci-tech information management system, but also to the development of scientific digital libraries in the world. © Emerald Group Publishing Limited.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/003-870-955-879-723 tex.type: [object Object]
Keywords: China; Digital libraries; Document management; Information services; National libraries; Worldwide web; dept.ils

Library preservation in Russia: hope and despair on the edge of the technological revolution - Popova‐Gosart, Ulia (Library Management, 2004)
The paper discusses the state of library preservation as the main problem of library management in Russia during the times of transition to digital environments. Today, Russia's extensive library system is undergoing a paradigm change toward the implementation of information technology (IT) to develop public access to information, that is perceived to be vital for the growth of the country. The first principal projects to elevate Russia to the ranks of the technologically advanced started as recently as 1990s, and, although having had some success, the country's digital resources remain grossly inadequate to support the growing public demand for information and education. Despite its state of retardation, the problems of preserving digital sources in Russia are evident to concerned specialists in the fields of informational science and archive work. Although these and other related problems are not addressed widely enough, they have gradually surfaced as an undeniable priority for the international preservation community. There is a promise to continue the necessary training and education that will link the national Russian library system with more collaborative projects and with leading international organizations. © 2004, Emerald Group Publishing Limited. All rights reserved.
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00246 tex.type: [object Object]
Keywords: Digital storage; Libraries; Russia; dept.ils

Managing the information revolution: library management, the control of prescriptive technologies, and the future of librarianship - Sierpe, Eino (Library Management, 2004)
This article seeks to promote a critical perspective on the present conceptualization of library management and the problems posed by technology. More specifically, it addresses the challenges faced by library administrators in relation to computing technologies. Through the adoption of Ursula Franklin's view of technology as “practice”, the article contrasts the practice of holistic and prescriptive technologies in library contexts. It also addresses the transformations of librarianship and the increasing adoption of prescriptive technological models. To exemplify the ongoing destruction of traditional librarianship, the three practices that comprise the fundamentals of librarianship are analyzed, namely, cataloging, collection development, and reference work. © 2004, Emerald Group Publishing Limited
3 citations (Crossref) [2023-10-31] Citation Key Alias: pop00170 tex.type: [object Object]
Keywords: Information management; Librarianship; Libraries; dept.ils

Best practices, standards and techniques for digitizing library materials: a snapshot of library digitization practices in the USA - Liu, Yan Quan (Online Information Review, 2004)
This study investigates current practice in digitizing library materials in the USA. Building a good digital collection has been a common task, pervasive in all types of libraries. Digitization becomes more and more crucial, affecting libraries while they work towards becoming digital. Researchers and practitioners would like to know what practices have been developed to deal with the challenges that pose the most significant problems or concerns for libraries in digitization. Through probing some widespread issues on what materials to digitize, and the associated standards and technologies in digitization in US libraries, this survey of current literature reveals a number of prominent library digitization practices, methods and challenges, and highlights the best practices, trends and interests in library digitization pertaining to both policy and technology marketplace issues.
17 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/059-597-493-339-542 tex.type: [object Object]
Keywords: Analog to digital conversion; Data processing; Digital libraries; Document image processing; Electronic media; Information and Library Science; Multimedia systems; Project management; Public policy; Societies and institutions; Standards; Technical problems; United States of America; dept.ils

Is the education on digital libraries adequate - Liu, Yan Quan (New Library World, 2004)
This study investigates the state of education for digital libraries. For this study, a Web survey was conducted of syllabi of courses on the subject of digital libraries (DL). Similarities and differences on such subjects as teaching emphases, course outlines, textbooks and assignments were compared. The majority of classes now contain a “hands-on” element, a practical component of the course that requires that the students interact with digital libraries. Not all of the course contents are up-to-date in the field of library and information technology. While the quality of DL education seems to have advanced at those schools and institutions that offer classes with “hands-on” requirements, the educational approach at many of the “hands-off” universities seems somewhat technophobic and overly dependent on outdated pedagogical methods. Those students who have received practical experience with digital libraries, like those provided in the “hands-on” courses, appear to be best served for future practice in the field of librarianship. © 2004, Emerald Group Publishing Limited
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/049-352-432-311-492 tex.type: [object Object]
Keywords: Digital libraries; Europe; Libararies; Library facilities; North America; Surveys; dept.ils

Preparation, microstructure and physical characteristics of ferroelectric pb 5 ge 3 O 11 thin films for memory application - Liu, Y. X.; Caragianis-Broadbridge, Christine; Lehman, A. H.; McGuinness, J. K.; Ma, Tso-Ping (MRS Proceedings, 2003)
We report sol-gel process of Pb5Ge3O11 (PGO) as well as the microstructure and physical properties of ferroelectric PGO films for memory applications. The PGO sol was prepared from lead acetate hydrate, germanium isopropoxide, and di(ethylene glycol) ethyl ether. The reactions taking place during the sol-gel process were examined in detail, Diethanolamine (DEA) was added to help maintain the desired species ratio and prevent germanium oxide precipitation. The preferred orientation of the PGO thin films was well controlled by the heating and reflux procedures in the sol-gel preparation process. Additionally, to examine the impact of post-deposition processing, selected samples were oxygen annealed at temperatures ranging from 450-650°C. The samples were characterized with X-ray diffraction (XRD), non-contact (planview) atomic force microscopy (NC-AFM). The resulting data indicate that the microstructure and physical properties of PGO films depend strongly on the precursor preparation as well as the post deposition annealing temperature.
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00135 tex.type: [object Object]
Keywords: Atomic force microscopy; Ferroelectric materials; Glove boxes; Isopropoxide; Lead compounds; Low-power memory; MISFET devices; Microstructure; Sol-gels; Thermal effects; Thin films; X ray diffraction; dept.ils

Where does professional education on digital libraries lead our new librarians - Liu, Yan Quan (International Conference on Asian Digital Libraries, 2003)
This study investigates the state of school education for digital libraries. For this study, a web survey was conducted of syllabi of courses on the subject of digital libraries. Similarities and differences on such subjects as teaching emphases, course outlines, textbooks and assignments were compared. The majority of classes now contain a "hands-on" element, a practical component of the course that requires that the students interact with digital libraries. Those students who have received practical experience with digital libraries, like those provided in the "hands-on" courses, are best served for future practice in the field of librarianship. © Springer-Verlag Berlin Heidelberg 2003.
0 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Digital libraries; E-learning; Education; Practical experience; Professional education; School education; Students; Teaching; Web surveys; dept.ils

Transformations of Librarianship in Support of Learning Communities - Sierpe, E.; De la Peña McCook, K. (Reference and User Services Quarterly, 2003)
Keywords: dept.ils; ⛔ No DOI found

The use of statistics in the managerial process by public library directors in China and the USA: a cross‐country survey - Liu, Yan Quan (Library Management, 2001)
Librarians have been involved in collecting and disseminating statistics for many years. Utilising statistics to describe and assess the operation of library activities as a part of library tradition has received growing attention from researchers, policymakers, library managers, and professionals. However, few studies have investigated how statistics are used in libraries. This report compares directors’ uses of statistics provided by national agencies in the USA and China to highlight the differences and similarities between the ways in which the two groups of directors make use of statistics, and the statistical information that directors find particularly useful. The results are intended to provide library administrators with an insight of how library statistics are used in the managerial process, and may also help the national statistical providers to obtain an understanding of the characteristics and pattern of use of their products. © 2001, MCB UP Limited
3 citations (Crossref) [2023-10-31] Citation Key Alias: pop00177 tex.type: [object Object]
Keywords: China; Libraries; Management; Public Libraries; Statistics; USA; dept.ils

The transition from paper to electronic journals: Key factors that affect scholars' acceptance of electronic journals - Kim, Hak Joon (Serials Librarian, 2001)
The primary purpose of this paper is to investigate what factors crucially affect scholar's acceptance of e-journals. Before reviewing various aspects of e-journals, it is necessary to fully understand the traditional journal system, because the developments, roles, and deficiencies of the paper journal system will illustrate some basic requirements for successful e-journals. This article also examines the developments of e-journals and presents a comprehensive examination of the economic, technological and cognitive, and sociological aspects of e-journals based upon an extensive literature review. With regard to the economic and technological and cognitive aspects, the benefits of scholarly e-journal publishing appear to be, by and large, favorable to the transition from paper to electronic journals. However, the major stumbling block is the credibility of scholarly e-journals. Whether or not scholars can obtain the same recognition or rewards through e-journal publication as they obtain through paper journal publication must be one of the key factors that affect scholar's acceptance of e-journals.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-081-770-161-36X tex.type: [object Object]
Keywords: Electronic journals; Journal functions; Journal system; Scholarly communication; Scientific reward system; dept.ils

A comparison of public library use of statistics – a cross‐country survey report - Liu, Yan Quan (New Library World, 2001)
Librarians have been involved in collecting and disseminating statistics for many years. Utilizing statistics to describe and assess the operation of library activities as a part of library tradition has received growing attention from researchers, policymakers, library managers, and professionals. However, few studies have investigated how statistics are used in libraries. This report compares directors’ uses of statistics provided by national agencies in the USA and China to highlight differences and similarities of the uses the two countries’ directors make of statistics and the statistical information that directors find particular useful. The results are intended to provide library administrators with an insight of how library statistics are used in the managerial process and may also help the national statistical providers to obtain an understanding of the characteristics and pattern of use of their products. © 2001, MCB UP Limited
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/154-713-030-974-661 tex.type: [object Object]
Keywords: China; Librarians; Libraries; Management; Statistics; USA; dept.ils

A dynamic model of museum and academic library cooperation - Reilly, Karen E; Verges, Jolene De (College & Undergraduate Libraries, 2001)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/187-608-446-797-462 tex.type: [object Object]
Keywords: dept.ils

Development of a web-based faculty publications database - Bai, S.; Kelly, P. (Bulletin of the Medical Library Association, 2000)
Keywords: Connecticut; Databases; Bibliographic; Faculty; Medical; Internet; Libraries; Medical; Publications; Universities; article; data base; dept.ils; education program; information system; library; publication; research; ⛔ No DOI found

Personalizing information retrieval using task features, topic knowledge, and task product - Liu, Jingjing (International ACM SIGIR Conference on Research and Development in Information Retrieval, 2009)
3 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: dept.ils

The impact of digital resource and service use on urban residents in new england public Libraries—A survey report - Liu, Yan Quan; Wnuk, Agnes (Public Library Quarterly, 2009)
Today, access to digital information is essential to patrons using public libraries, whether they have contact with computers at home, work or school or whether the public library is their only contact. In order to evaluate and ultimately enhance public library digital resources and services, it is critical for administrators, librarians and digital information architects to recognize the impact their current digital offerings have on users. This study utilizes a survey to gauge the perceptions of patrons who use digital resources and services in six urban New England public libraries as part of ongoing research into digital information access in public libraries in the United States from the perspective of users.
3 citations (Crossref) [2023-10-31] tex.ids: lens.org/052-608-977-611-377 tex.type: [object Object]
Keywords: Digital divide; Digital libraries; Digital resources; Digital resources services; New England public libraries; Public libraries; Urban libraries; dept.ils; peer-reviewed

Exploiting the social style of patrons to improve their satisfaction with the reference interview - Sisselman, Peggy (Library Review, 2009)
Purpose: The purpose of this paper is to discover whether the social styles of patrons affects their perception (and librarians' perception) of the quality of the reference interview. Also, whether learning to assess social styles of patrons improves perception of the quality of the reference interview. Design/methodology/approach: The researcher observed 24 reference interviews, assessed the social style of each patron using a checklist of behavioral characteristics; both patrons and librarians confidentially filled out a survey to assess the outcome of the reference interview. Findings: It appears that the social style of patrons has some effect on how both librarians and patrons perceive the outcome of the reference interview. There also appears to be a correlation between the librarians' awareness of the social styles of people and the outcome of the reference interview. Practical implications: Literature has not provided any data on how social style theory on the four social styles (analytical, expressive, driver, amiable) could be used to improve the reference interview. Originality/value: Social style theory has been explored in academic settings and in the areas of marketing and sales, but not yet in public libraries. © Emerald Group Publishing Limited.
4 citations (Crossref) [2023-10-31] tex.ids: lens.org/128-369-272-495-02X tex.type: [object Object]
Keywords: Customer satisfaction; Individual perception; Interpersonal communications; Reference services; Social dynamics; dept.ils

Enhancing digital information access in public libraries - Ayers, Kathleen; Liu, Yan Quan (Proceedings of The Asist Annual Meeting, 2007)
Purpose To explore the impact of public digital library resources on urban residents, to elucidate the current usage patterns of public digital library resources/services and levels of satisfaction with the resources/content in urban digital libraries and make recommendations as to steps that would improve service to this population. Design/Methodology/Approach We conducted an anonymous user-completed survey study of 6 urban libraries to collect demographic and information regarding satisfaction with Digital Library (DL) resource and patterns of use. Findings Our respondents represented a cross section of races, genders, ages, and educational backgrounds. Our results in this much-needed area of study demonstrate that libraries should plan to provide more access, less filtering, regular upgrades, and more training to use the resources. Practical Limitations/Implications Larger studies should be used to follow up this report, in order to be able to obtain a generalized understanding of overall patterns of urban residents using DLs in public settings. Recruitment techniques did not adequately sample potential (but not current) DL users. Originality/Value This study contributes to a scant empirical data set addressing the impact that access to public digital information and services have on urban residents. We offer new data and recommendations that will guide public library administrators in enhancing the impact, efficiency and value of public DL resources/services to improve the digital learning environment for life-long educaiton at all levels in a broad community of urban users.
0 citations (Crossref) [2023-10-31] tex.ids: lens.org/027-715-068-622-316 tex.type: [object Object]
Keywords: dept.ils; ⛔ No DOI found

Developing an integrated public library service in Dongguan, one of China's fastest growing cities - Liu, Yan Quan; Li, Donglai (New Library World, 2007)
Purpose - The purpose of this case study is to explore the construction pattern and issues involved in the development of an urban library service system in China. Design/methodology/approach - This study was conducted through an analytical evaluation of the development of an integrated public service system and its distribution of information among libraries and information centers in an urban community. Findings - Constructing an integrated public service system is an important trend in urban libraries in the new millennium. Drawing from the Dongguan library's integrated public service system that aims to master better various resources from whole service area, this text summarizes technology innovation and the significant results of the Dongguan library system redevelopment, providing an absorbing insight into developments in the Chinese public library service. Originality/value - While the ultimate goal of integration is to provide better services to meet the information-seeking needs of urban residents, it is necessary to meet these needs through a technological breakthrough in the administration of clustered libraries, to instill a central branch system, and to work out the advantages of group service.
0 citations (Crossref) [2023-10-31] tex.ids: lens.org/074-087-094-612-648 tex.type: [object Object]
Keywords: China; Digital libraries; Library management Public sector organizations; Public libraries; dept.ils

Digital information access in urban/suburban communities: A survey report of public digital library use by the residents in Connecticut - Liu, Yan Quan; Martin, Craig; Roehl, Eileen; Yi, Zhixian; Ward, Sheila (OCLC Systems and Services, 2006)
Purpose - The purpose of this paper is to explore the impact of public digital services on urban/suburban residents, to uncover the current usage of public digital services and levels of satisfaction with the digital resources/content in urban digital libraries (networked computers with specific information infrastructure designed free for public use). Design/methodology/approach - A qualitative approach is used as a main stream in the research framework as the method of inquiry. Qualitative one-to-one interviews include surveying users who use public library websites, observing the users, consulting librarians about the users, and interviewing the users. Findings - Provides demographic patterns of the patron's interaction with the digital services public libraries provide, and the satisfaction and compliances the residents have regarding information access through the digital technology in urban/suburban Connecticut. Practical implications - Because of the small number of participants, this study has limitations in being generalized to an understanding of overall patterns of urban residents using digital resources in public settings in the USA or elsewhere, however, it could be a good pilot study for a nation-wide survey with the methods tested. Originality/value - This study helps fulfill the scant empirical attention given to the impact access to public digital information or use of digital library services on the urban/suburban residents, offers new data that help public library administrators enhance the impact, efficiency and value of the public digital library services to improve the digital learning environments for life-long education at all levels in a broad community of urban-suburban users. © Emerald Group Publishing Limited.
5 citations (Crossref) [2023-10-31] tex.ids: lens.org/051-401-327-795-077 tex.type: [object Object]
Keywords: Design/methodology/approach; Digital learning environment; Digital libraries; Digital technologies; Information retrieval; Information services; Information studies; Life-long educations; Public libraries; Public library; Qualitative approach; Specific information; Surveys; dept.ils

The use of national public library statistics by public library directors - Liu, Yan Quan; Zweizig, Douglas L (The Library Quarterly, 2001)
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/008-574-806-615-498 tex.type: [object Object]
Keywords: dept.ils; ⛔ No DOI found